2014
DOI: 10.1089/sur.2012.227
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Immunoglobulin-Induced Neutrophil Apoptosis in the Lung during Murine Endotoxemia

Abstract: A therapeutic IVIg dose can attenuate neutrophil accumulation and regulate neutrophil apoptosis in the lung during endotoxemia. It is possible that the pathways by which IVIG induces neutrophil apoptosis may differ depending on the IVIg concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…This leads to secondary organ sequestration and lung infiltration by activated PMNs, which leads to lung injury and ARF. 25,27,28 Our results are in line with these findings, indicating that the inflammatory response is more strongly associated with ARF than with dysfunction of other organs, at each time point of the assessment. Furthermore, in agreement with previous studies, we noted that the most profound impact of inflammation on ARF was on the third day after OHCA.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This leads to secondary organ sequestration and lung infiltration by activated PMNs, which leads to lung injury and ARF. 25,27,28 Our results are in line with these findings, indicating that the inflammatory response is more strongly associated with ARF than with dysfunction of other organs, at each time point of the assessment. Furthermore, in agreement with previous studies, we noted that the most profound impact of inflammation on ARF was on the third day after OHCA.…”
Section: Discussionsupporting
confidence: 89%
“…26,27 Furthermore, two studies have suggested that the endothelium of the pulmonary microvasculature may play an active role in regulating the priming and de-priming of PMNs during their transit through the systemic circulation, as a 'gatekeeper' of a systemic inflammatory response. 25,27,28 In the case of global distress like PCAS, priming and activation of PMNs might overwhelm protective endogenous de-priming capacities of the lungs. According to this theory, I/R injury causes lung endothelial dysfunction and increased capillary permeability in the first stage of PCAS.…”
Section: Discussionmentioning
confidence: 99%
“…IVIG was shown to contain Fas and Siglec-9 specific antibodies, which can induce apoptosis in human neutrophils [ 28 , 34 , 35 ]. In murine neutrophils, IVIG (supplied by the Japan Blood Products Organization, Osaka, Japan; 0.3 and 1 g/kg, administered intraperitoneally) was reported to limit inhibition of neutrophil apoptosis induced by lipopolysaccharide (LPS) stimulation, potentially by blocking LPS-mediated effects, although no direct pro-apoptotic activity of IVIG could be demonstrated [ 36 ]. We therefore examined whether F(ab’) 2 fragments induce apoptotic cell death in murine neutrophils as a potential mechanism contributing to the protective effect of IVIG during EAE development.…”
Section: Resultsmentioning
confidence: 99%
“…The pulmonary endothelium plays an active role in regulating the priming of PMNs during their transit through the systemic circulation (Aoyama-Ishikawa, et al 2014, Singh, et al 2012). In the mouse model of sepsis, the pro-inflammatory milieu caused by endotoxin challenge impairs lung-mediated PMN de-priming, resulting in their accumulation, priming, release to the systemic circulation.…”
Section: Discussionmentioning
confidence: 99%